Bioactive compounds, bio‐functional properties, and food applications of Garcinia indica: A review. Issue 10 (7th August 2022) - Desai, Sahil; Sharma, Poorva; Kashyap, Piyush; Choudhary, Bharti; Kaur, Jasleen
Abstract: Garcinia indica Choisy (kokum), a plant from Clusiaceae family, is an underexplored fruit tree in the Western Ghats region. Kokum has been studied for its health benefits, associated with numerous bioactive compounds, including phenolic acids, flavonoids, citric acids, and others. Among all, garcinol, hydroxycitric acid, and anthocyanins (cyanidin‐3‐glucoside and cyanidin‐3‐sambubioside) are major bioactive compounds. G. indica fruit and fruit rinds have been reported to possess numerous therapeutic applications in various health conditions such as cancer, inflammation, diabetes, obesity, cardiovascular disease, and neurologic disorders. In this review, information has been provided on the bioactive compounds present in kokum and their significant health benefits. In vitro and In vivo studies of bioactive components on various diseases have also been reported. The limited information about human studies and G. indica fruit and fruit rinds is also presented. Practical applications: Bioactive compounds present in Garcinia indica can be utilized for nutraceutical preparations. G. indica can be added to food products to make them functional foods. Extraction of bioactive compounds can be done on an industrial scale. Bioactive compounds can be extracted and used to commercialize lifesaving drugs. Abstract : Garcinia indica (kokum) is a rich source of bioactive compounds such as phenolic acids, flavonoids, citric acids and others. Garcinol, hydroxycitric acid, and anthocyanins (cyanidin‐3‐glucoside and cyanidin‐3‐sambubioside) are major bioactive compounds. Owing to the presence of numerous bioactive compounds, it can be used for therapeutic applications.